Penggunaan Kulit Sintetis Sebagai Media Pembuatan Tas Ecoprint Menggunakan Daun Jati dan Bunga Kamboja - Sulaiman, Najmawati; Ninis; Darmawan (P3M Politeknik Negeri Media Kreatif, 2024)
Ecoprint products generally use fabric media in their manufacture, but there are still a few ecoprint products that are made using synthetic leather media. Therefore, it is necessary to make ecoprint bags that use synthetic leather as a medium. Teak leaves and frangipani flowers function as patterns and coloring agents for the products. The purpose of this writing is to make ecoprint bags using synthetic leather as a medium, teak leaves and frangipani flowers. The methods used include mordanting activities, ecoprint processes and product manufacturing. The product produced is an ecoprint bag made from synthetic leather, the purple color comes from teak leaf dye and the yellow comes from the color and pattern of frangipani flowers. The ecoprint leather bag measures length x width x height, namely 20x5x15 cm, using 7 teak leaves and 5 frangipani flowers. The conclusion is that color pigments derived from plants can be used as natural dyes and attractive patterns on synthetic leather ecoprint media.